Between emptiness and superfluity: funeral photography and necropolitics in late-apartheid South Africa. (2nd January 2022) - Bethlehem, Louise; Musih, Norma
Abstract : Documentary photography has undergone a process of devaluation in post-apartheid South Africa. In response, Patricia Hayes has introduced the term "empty photographs" into the scholarly conversation, using it to designate images that have been derided as "'bad, ' 'boring, ' or repetitious" in post-apartheid settings ("The Uneven Citizenry, " 189). This article revisits a subset of such images to contest their seeming emptiness—pallbearers escorting dead activists to their graves during political funerals in late-apartheid South Africa. Focusing specifically on Afrapix photographer, Gille de Vlieg's images of Themba Dlamini's funeral in Driefontein in 1990, the paper restores their local history to view and unpacks the visual cultural and material cultural circuits of militant mourning in which they were embedded. It then uses various orders of metonymy in the visual field to comment on the "necropolitics" of the apartheid regime (Achille Mbembe, "Necropolitics"). The paper concludes with a reflection on Ariella Azoulay's notion of the "civil gaze" (Civil Imagination) and considers what unfolds when a reckoning with the differential distribution of death that characterizes necropower reorients this faculty away from the individual photograph towards series, genre or corpus.